2016
DOI: 10.1111/jvh.12520
|View full text |Cite
|
Sign up to set email alerts
|

Matched population‐based study examining the risk of type 2 diabetes in people with and without diagnosed hepatitis C virus infection

Abstract: Meta-analyses have found hepatitis C virus (HCV) infection to be associated with an increased risk of type 2 diabetes mellitus (T2DM). Here, we examine this association within a large population-based study, according to HCV RNA status. A data-linkage approach was used to examine the excess risk of diagnosed T2DM in people diagnosed with antibodies to HCV (anti-HCV) in Scotland (21 929 anti-HCV(+ves) ; involving 15 827 HCV RNA(+ves) , 3927 HCV RNA(-ves) and 2175 with unknown RNA-status) compared to that of a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The liver is crucial to carbohydrate metabolism and glucose homoeostasis, and hepatic dysfunction causes glucose abnormalities that can lead to the development of DM, which is prevalent in chronic liver disease patients . Non‐alcoholic fatty liver disease, alcoholic liver disease and HCV infection have been found to be strongly associated with T2DM . However, the relationship between HBV infection and T2DM remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver is crucial to carbohydrate metabolism and glucose homoeostasis, and hepatic dysfunction causes glucose abnormalities that can lead to the development of DM, which is prevalent in chronic liver disease patients . Non‐alcoholic fatty liver disease, alcoholic liver disease and HCV infection have been found to be strongly associated with T2DM . However, the relationship between HBV infection and T2DM remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Non-alcoholic fatty liver disease, alcoholic liver disease and HCV infection have been found to be strongly associated with T2DM. [35][36][37] However, the relationship between HBV infection and T2DM remains controversial. Cai et al (2014) performed a meta-analysis that indicated that patients with HBV infection were at a higher risk of developing DM when compared with patients without HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study of 15,128 adults in the United States showed no significant association between HCV and T2DM (27). A more recent population-based study of 21,929 anti-HCV-positive patients in Scotland did not find evidence to indicate that HCV infection conveyed an increased risk of T2DM (28).…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 96%
“…In contrast, elevated alanine aminotransferase and gamma glutamyltransferase were associated both with DM and IR, regardless of HCV status . In a Scottish population‐based study performed among 21 929 adults with positive HCV serology, including 15 827 with chronic hepatitis C, and compared to 65 074 subjects with negative HCV serology (matched for gender, age and postcode), chronic HCV infection was not associated with an excess risk of diagnosed DM at the population level . Finally, in a Southern Italian cohort of 2472 adults from the electoral register followed between 1985 and 2005, no association was found between incident DM and positive HCV serology .…”
mentioning
confidence: 95%